Rasch‐ionale for neurologists. Issue 3 (September 2015) - Vanhoutte, Els K.; Hermans, Mieke C. E.; Faber, Catharina G.; Gorson, Kenneth C.; Merkies, Ingemar S. J.; Thonnard, Jean‐L.; on behalf of the PeriNomS Study Group; Barreira, A.A.; Bennett, D.; Hadden, R.D.; Hughes, R.A.C.; Lunn, M.P.T.; et al.
Abstract Outcome measures are considered the most important tools to monitor patients' outcome in both clinical and research settings. Measuring the clinical state of patients is a fundamental part of our daily clinical practice and research that sometimes is taken for granted. In peripheral neuropathies, there are many scales available, but most of these are at the ordinal level. This paper will systematically address the types of scales available (being nominal, ordinal, interval, or ratio data‐based) in terms of their strengths and weaknesses. The differences between classical test theory‐based and modern test method‐based outcome measures will be addressed with emphasis on Rasch methodology. Various steps will be highlighted as part of the evaluation and construction of outcome measures using the Rasch method, with the aim to increase the knowledge and utility of this technique. We argue that Rasch‐built outcome measures should be used for future studies in neuromuscular disorders and their method of construction could be easily extrapolated to other neurological illnesses.